Perspectivas mundiales - Sarmiento, Eduardo (Diario El Espectador, 2011)
Los hechos económicos sobresalientes del año giraron en torno a la incapacidad de los líderes para reactivar y estabilizar la economía mundial. Los círculos influyentes estadounidenses predecían que en 2011 el producto nacional crecería 3,5% y entraría en franca recuperación; la información más reciente señala que apenas llegará a 1,5%.

The outstanding economic events of the year revolved around the inability of leaders to revive and stabilize the world economy. Influential circles in the United States predicted that in 2011 the national product would grow 3.5% and would enter into a clear recovery; the most recent information indicates that it will barely reach 1.5%.
Keywords: Crisis económica; Economía internacional; Política económica; Economic crisis; International economy; Economic policy